Science education in the Anthropocene: the aesthetics of climate change education in an epoch of uncertainty - Ferguson, Joseph Paul; White, Peta J. (Frontiers in Education, 2023)
We have a responsibility as science educators to work with young people to enact education that enables collective rebalancing of relationships between humans and more-than-humans that are disturbed by human-induced climate change. However, to date, climate change education has not been prioritised in school science at a policy, curricula, classroom and community level, due to an aesthetic which does not sufficiently value climate science or recognise the social impacts of science as part of the discipline.